Chapter The Design of Work-Related Teaching & Learning Methods: Case Studies and Methodological Recommendations - Frison, Daniela (Studies on Adult Learning and Education, 2018)
What kind of Work-Related activities/programmes do Italian teachers propose to their students? What are common elements considered in the designing of Work-Related activities by those proposing them? A multiple case study research programme was chosen as a method to explore the current Italian situation regarding Work-Related teaching and learning methods in Higher Education (Coll et al. 2008; Dirkx 2011) and to define some possible methodological recommendations to encourage the design of Work-Related Learning activities/programmes